2003
DOI: 10.1128/jb.185.17.5220-5233.2003
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Broad-Host-Range Vibriophage KVP40: Comparative Genomics of a T4-Related Bacteriophage

Abstract: The complete genome sequence of the T4-like, broad-host-range vibriophage KVP40 has been determined. The genome sequence is 244,835 bp, with an overall G؉C content of 42.6%. It encodes 386 putative proteinencoding open reading frames (CDSs), 30 tRNAs, 33 T4-like late promoters, and 57 potential rho-independent terminators. Overall, 92.1% of the KVP40 genome is coding, with an average CDS size of 587 bp. While 65% of the CDSs were unique to KVP40 and had no known function, the genome sequence and organization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
197
4
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(219 citation statements)
references
References 56 publications
(50 reference statements)
5
197
4
4
Order By: Relevance
“…The gene encoding Haemophilus Nampt, nadV, is carried on a plasmid called pNAD1 (30), which has recently been found to contain homologs of the genes originated from a single-stranded bacteriophage (45). Most surprisingly, the entire pyridine nucleotide salvage cycle containing genes homologous to Nampt, Nmnat, and Sir2 has been found in the T4-like, broad host range vibriophage KVP40 (46). Based on these findings, the functional connection between NAD biosynthesis mediated by Nampt and Sir2 seems ancient and fundamental.…”
Section: Discussionmentioning
confidence: 88%
“…The gene encoding Haemophilus Nampt, nadV, is carried on a plasmid called pNAD1 (30), which has recently been found to contain homologs of the genes originated from a single-stranded bacteriophage (45). Most surprisingly, the entire pyridine nucleotide salvage cycle containing genes homologous to Nampt, Nmnat, and Sir2 has been found in the T4-like, broad host range vibriophage KVP40 (46). Based on these findings, the functional connection between NAD biosynthesis mediated by Nampt and Sir2 seems ancient and fundamental.…”
Section: Discussionmentioning
confidence: 88%
“…These include Pseudomonas aeruginosa phage KZ (280 kbp, Mesyanzhinov et al, 2002), EL (211 kbp, Herveldt et al, 2005), and PA3 (309 kbp, Monson et al, 2011), Vibrio parahaemolyticus phage KVP40 (245 kbp, Miller et al, 2003), Stenotrophomonas maltophila phage SMA5 (250 kbp, Chang et al, 2005), and Yersinia enterocolitica phage R1-37 (270 kbp, Kiljunen et al, 2005). Jumbo phages were also reported for Sinorhizobium meliloti (phage N3, 207 kbp, Martin and Long, 1984) and Bacillus megaterium (phage G, 670 kbp, Sun and Serwer, 1997).…”
Section: Rsl Phages Of the Myoviridaementioning
confidence: 99%
“…The role of T4 Rnl2 in vivo is unclear. Vibriophage KVP40, which we show specifies a Pnkp enzyme, encodes its own homologs of both Rnl1 and Rnl2 (41,54). The provocative correlation is that Omega and Cjw1, which are distinguished from other mycobacteriophages by their possession of a Pnkp enzyme, are also unique among the mycobacteriophages in their specification of putative Rnl2-like ligases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). The conservation of Pnkp in KVP40 is notable given that only 26% of the predicted KVP40 proteins have homologs in phage T4 and only 36% of T4 proteins have homologs in KVP40 (41). The genome sequences of 10 mycobacteriophages isolated from diverse niches by selection for lytic growth in Mycobacterium smegmatis (40) revealed that two of these DNA viruses, Omega and Cjw1, also encoded putative homologs of T4 Pnkp.…”
Section: New Bacteriophage Homologs Of T4 Pnkp-mentioning
confidence: 99%
See 1 more Smart Citation